PENGARUH POSITIONING PRODUK TERHADAP LOYALITAS PELANGGAN (Kasus penjualan produk Brand Wardah pada PTI. Wardah Distributor Cabang Pekanbaru) - Agusma, Mesi; Heriyanto,, Meizy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research was conducted PTI . Wardah Distributor Branch Pekanbaru. The setting of the problem is how to influence the loyalty of the customers' product positioning on PTI .Wardah Distributor Branch Pekanbaru . The purpose of this study was to determine the effect of positioning the product to the customers' loyalty to the PTI .Wardah Distributor Branch Pekanbaru. The author uses descriptive quantitative analysis method and some theories about product positioning and Loyalty . Indicators used in the independent variable is the hallmark product , price and quality , pengguaan or functionality, users of the product and the dependent variable is the level of loyalty and purchasing patterns. Data collection using questionnaires and interviews . The sample used was purposive sampling . Source of data used is primary data or data obtained directly from the questionnaires and interviews . Secondary data is data obtained from company documents PTI .Wardah Distributor Branch Pekanbaru . The results of this study indicate that the influence of the variable product positioning to Customer Loyalty . And the existence of a strong relationship between the variables of the product Positioning Strategy Customer Loyalty. Keywords : Product Positioning , Loyalty , and Distributors.